2015
DOI: 10.1002/elan.201400563
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Nitrite Determination Using Iron Phthalocyanine Modified Gold Nanoparticles

Abstract: The inside cover picture shows the catalytic degradation of a stem‐loop motif of the structured hepatitis C IRES RNA in an HCV‐infected liver cell. Catalytic metallodrugs promote irreversible degradation of the RNA and demonstrate significant antiviral activity in a cellular HCV replicon assay. MALDI‐TOF mass spectrometry combined with computational analysis provides insights into the site‐specific cleavage mechanism. For more details, see the Full Paper by James A. Cowan et al. on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 57 publications
(46 reference statements)
1
18
0
2
Order By: Relevance
“…Such behavior suggests the adsorption/pre-concentration ability of the modified layers toward NaNO 2 . Poor current response in the case of GC is related to sluggish kinetics for nitrite oxidation as previously reported for this material [7,20]. Among the electrodes studied here, the GC/C 22 TMA-ASC showed the highest voltammetric peak.…”
Section: +supporting
confidence: 66%
See 1 more Smart Citation
“…Such behavior suggests the adsorption/pre-concentration ability of the modified layers toward NaNO 2 . Poor current response in the case of GC is related to sluggish kinetics for nitrite oxidation as previously reported for this material [7,20]. Among the electrodes studied here, the GC/C 22 TMA-ASC showed the highest voltammetric peak.…”
Section: +supporting
confidence: 66%
“…Various redox mediators such as metalled phthalocyanines or porphyrazines were used to build nitrite sensitive modified electrodes. In particular, macrocycles bearing transition metal ions such as Co, Fe, and Ni in their cores and involving reversible redox transitions are considered to be suitable for nitrite determination [3,7,[18][19][20]. Recently, composites consisting of graphene nanoparticles and precious metal have also been given attention [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Functionalization of nanomaterials with phthalocyanines has also been widely used to prepare electrochemical sensors. The number of papers in this field is quite It has been demonstrated that the combination of MPcs with gold nanoparticles (AuNPs) can improve the catalytic properties of the electrodes [37][38][39][40]. Similarly, electrochemical sensors have been developed by combining phthalocyanines with carbon nanotubes on carbon electrodes [41][42][43][44].…”
Section: Improvement Of the Performance Through The Use Of Nanomaterials And Nanostructured Filmsmentioning
confidence: 99%
“…Metallophthalocyanine (MPc) have a high chemical and thermal stability, electrical and optical properties and rich coordination chemistry. With these properties, MPc ionophore become one of the most interesting materials in the fabrication of chemical sensors for the selective recognition and sensing of cations and anions . Cobaltphthalocyanine (CoPc) belongs to the class of MPcs which are widely studied and used in the literature, due to their interesting physico‐chemical and recognition properties .…”
Section: Introductionmentioning
confidence: 99%